ATHLETES DEVELOPMENT MANAGEMENT AT STATE HIGH SCHOOL SPORTS (SMANOR) - Rahmah Rahmah; Delvi Kristanti Liloi; Abu Bakar; Didik Purwanto (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2023)
SMANOR Tadulako is a new sports-gifted school in Central Sulawesi Province. Within three years, almost all sports have started to show results, both at the regional and national levels. Of course, there is good cooperation between administrators, coaches, athletes, and other parties. Researchers took descriptive qualitative research to see the management of athlete development at SMANOR Tadulako, Central Sulawesi Province. The purpose of this study was to analyze the management functions of Planning, Organizing, Movement, Supervision, and Evaluation at Tadulako Senior High School, Central Sulawesi Province. The results of the study: stewardship seen from the management function 1) Planning is Very Good, 2) Organizing is Very Good, 3) Movement is Good, 4) Supervision is Very Good and 5) Evaluation is Very Good. Activity Program 1) Good Planning, 2) Very Good Organizing, 3) Good Movement, 4) Very Good Supervision, and 5) Very Good Evaluation. Facilities and Infrastructure 1) Good Planning, 2) Fairly Good Organizing, 3) Good Movement, 4) Good Supervision, and 5) Fairly Good Evaluation. Funding is categorized as Fairly Good. The conclusions of this study are 1) management is categorized as Good, 2) Program activities are Good, 3) Facilities and infrastructure are quite good and 4) Funding is quite good. Based on the results of the research, it can be concluded that to achieve management of facilities and infrastructure, it is necessary to carry out planning, organization, movement, monitoring, and evaluation in the management of athlete development.